INCIDENCE RATES OF GENITAL PROLAPSE IN WOMEN OF REPRODUCTIVE AGE - Shavkatov Xasan Shavkatovich (Web of Journals Publishing, 2025)
Prolapse of genital organs is a common condition among gynecological diseases, with clinical symptoms manifesting early in 28%-39% of cases. Recent studies have shown a concerning trend of younger women, including those of reproductive age, being increasingly affected by this condition. The prevalence of genital prolapse has been reported as 10.1% in women under 30, 40.2% in women between 30 and 45, and up to 50% in women over 50 years of age [C.H. Kim, 2017; Lucot, J.P., 2018; Bejenar V.F., 2013].Pelvic floor musculature deficiency, a leading cause of genital prolapse, presents a significant medical and socio-economic challenge. While previously considered a condition primarily affecting older women, the progressive nature of the disease and its rising prevalence among younger women necessitate increased attention. This trend has profound implications not only for the physical health of women in their reproductive years but also for their psycho-emotional well-being. The need for surgical intervention among women of reproductive age underscores the urgency of addressing this issue. This paper explores the prevalence, clinical progression, and multifaceted impact of genital prolapse, emphasizing the importance of early diagnosis and comprehensive treatment strategies to mitigate its effects on affected individuals and society at large.
Keywords: Genital prolapse, reproductive age, transvaginal hysterectomy, cystocele, rectocele.